Experimental investigation of SiC nanofluids for solar distillation system: Stability, optical properties and thermal conductivity with saline water-based fluid. (April 2017) - Chen, Wenjing; Zou, Changjun; Li, Xiaoke; Li, Lu
Highlights: Salt concentration effect on nanofluids was found. SiC nanofluid was proposed as a potential alternative in solar energy system. The luminousness of 0.4 vol% SiC nanofluids was less than 1%. The thermal conductivity of seawater based nanofluid was enhanced about 5.2%. Abstract: Modified solar distillation system with different nanofluids was an emerging application area, which added various nanoparticles in saline water to enhance the ability of solar energy absorption and storage. However, there are lacked of exploration with the performance of nanofluids with saline water. Therefore, the stability, optical properties and thermal conductivity of SiC/saline water based nanofluids were systematically investigated in this study. The experimental results showed that SiC nanofluids have good effects for enhancing the thermal conductivity with respect to base fluids (>6% increase at 0.4 vol% SiC nanofluids) and have good capacity of solar absorption (<1% luminousness at 0.4 vol% SiC nanofluids). With increase of salt concentration, some negative effects will affect nanofluids both in stability and thermal conductivity. Therefore, an appropriate salt concentration range and nanoparticles load should be measured in practical application. Moreover, 0.4 vol% SiC nanofluid was prepared with natural seawater and had sufficient stable period. The thermal conductivity of seawater based nanofluid was enhanced about 5.2% with respect to base fluid. Good stability, low luminousness and effective thermal property of SiC nanofluids confirmed the feasibility of nanofluids application in solar distillation system.